If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = 2x + 4y Solving 4x = 2x + 4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 4x + -2x = 2x + -2x + 4y Combine like terms: 4x + -2x = 2x 2x = 2x + -2x + 4y Combine like terms: 2x + -2x = 0 2x = 0 + 4y 2x = 4y Divide each side by '2'. x = 2y Simplifying x = 2y
| 61=c+54 | | a/.5=2 | | v+-10=-5 | | 17=u-16 | | Y-4=-1x+3 | | 59=5y-11 | | 180=30+123+b | | 9=n+4 | | 2x+4+6X=-68 | | 9=2+4 | | 180=(16x-3)+45 | | 38=6x+6x-10 | | 29=6 | | -11=p-17 | | 4x-6+5x=57 | | 9=3g | | 180=16x-3+45 | | 5x+1-2x=27 | | 0.75y=2x-6 | | 2(y+2)-8=0 | | -4x^2+19x=-320 | | x+1-4x=13 | | 5/8q=-20 | | 8x-13y=12 | | Y-5=m(x-6)form | | -18=-x-11 | | 8y+y^2=180 | | 8y+y^2=189 | | 0.54(6)+.06x=.18(24+x) | | f(4)=9x+7 | | -8+6x+4x=-98 | | 13x+1=9x+5 |